Hierarchical 3D SERS substrates fabricated by integrating photolithographic microstructures and self-assembly of silver nanoparticles - Zhang, Qi (2014)
Most of the surface-enhanced Raman scattering (SERS) substrates are 2D planar systems, which limits the SERS active area to a single Cartesian plane. Here, we fabricate 3D SERS substrates with the aim to break the traditional 2D SERS active area limitation, and to extend the SERS hotspots into the third dimension along the z-axis. Our 3D SERS substrates are tailored with increased SERS hotspots in the z-direction from tens of nanometers to tens of micrometers, increasing the hotspots in the z-direction by at least an order of magnitude larger than the confocal volume (∼1 μm) of most Raman spectrometers. Various hierarchical 3D SERS-active microstructures are fabricated by combining 3D laser photolithography with Langmuir-Blodgett nanoparticle assembly. 3D laser photolithography creates microstructured platforms required to extend the SERS-active area into 3D, and the self-assembly of Ag nanoparticles ensures homogeneous coating of SERS-active Ag nanoparticles over the entire microstructured platforms. Large-area 3D Raman imaging demonstrates that homogeneous signals can be collected throughout the entire 3D SERS substrates. We vary the morphology, height, and inclination angles of the 3D microstructures, where the inclination angle is found to exhibit strong influence on the SERS signals. We also demonstrate a potential application of this hierarchical 3D SERS substrate in information tagging, storage and encryption as SERS micro-barcodes, where multiple micro-barcodes can be created within a single set of microstructures.